USING THE NEAREST NEIGHBOR TECHNIQUE TO EVALUATE THE LOCATION DISTRIBUTION OF PUBLIC HOSPITALS IN DHI QAR GOVERNORATE - M.M. Raed Faiq Hassan; M. M. Ahmed Mohamed Hammoud; Ahmed Mohammed Hammood (Scholar Express Journals, 2024)
The research aims to explain the current distribution of public hospital sites in Dhi Qar Governorate, and to clarify the pattern of their distribution and the degree of their concentration and spread. The study relied on the dimension factor represented by the distance separating the administrative units of the governorate as a quantitative criterion as it is a major and important factor in the comparison between alternatives for choosing the service location, especially the locations of health facilities. The nearest neighbor technique has been relied upon as a statistical method through which accurate distribution patterns can be reached in determining the current distribution of hospitals at the governorate level, due to its importance in setting development plans and searching for the best ways to redistribute health institutions in a more balanced manner. The research reached the conclusion that public hospitals in Dhi Qar Governorate are distributed widely and at irregular distances. This explains the current actual distribution of these institutions, as they are distributed at the level of administrative units (districts only) and at the rate of one hospital for each district, with the exception of the governorate center represented by the city of Nasiriyah, which is five Hospitals.
Keywords: Location selection; nearest neighbor; service location